Research Literacy Workshop for Indonesian Language Teachers: Designing Scientific Inquiry-Based Explanatory Text Learning from Reliable Sources - Damayanti, Deasy Aditya; Yosep, Yosep Tri Nur; Mariyana, Tina; Medianingsih, Sri Mariyana; Suhartati, Suhartati Mariyana; Marfuah, Siti Mariyana; Nurafni, Sinta; Rahmasya AS, Shela Siti; Fitriani, Sakinah Siti (Indonesian Journal of Community Empowerment (IJCE), 2024)
This descriptive study explores the implementation of the "Research Literacy Workshop for Indonesian Language Teachers," focusing on designing explanatory text learning based on scientific investigation using credible sources. The workshop aimed to enhance teachers’ competencies in integrating research literacy into classroom practices, enabling students to develop critical thinking and scientific reasoning skills. Data were collected through observations, participant reflections, and document analysis. Findings indicate that teachers increasingly incorporate credible sources and investigative approaches in lesson planning, fostering more interactive and inquiry-based learning experiences. The study concludes that such workshops are essential for equipping educators with practical strategies to improve students’ understanding of explanatory texts through research-oriented methods.